A New Construction for Linkable Secret Handshake. (14th November 2019) - Tian, Yangguang; Li, Yingjiu; Deng, Robert H; Li, Nan; Yang, Guomin; Yang, Zheng
Abstract: In this paper, we introduce a new construction for linkable secret handshake that allows authenticated users to perform handshake anonymously within allowable times. We define formal security models for the new construction, and prove that it can achieve session key security, anonymity, untraceability and linkable affiliation-hiding. In particular, the proposed construction ensures that (i) anyone can trace the real identities of dishonest users who perform handshakes for more than k times; and (ii) an optimal communication cost between authorized users is achieved by exploiting the proof of knowledges.